ANALISIS KUALITAS PERAIRAN SUNGAI SUBAYANG BERDASARKAN INDEKS BIOTILIK SEBAGAI PENGAYAAN MODUL MATA KULIAH EKOLOGI PERAIRAN - Nur Ikhlas Syuhada; Suwondo '; Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The study was conducted to determine the quality of the waters of theSubayang as enrichment Aquatic Ecology module in November 2015 - January 2016.Stages of the research is the analysis of water quality based on the Biotilic indexSubayang River, the next stage of enrichment courses Aquatic Ecology modules usingADDIE models. The research found 25 familia divided into 8 orders in which the threeorders of groups EPT is the order Ephemeroptera (4 familia), Plecoptera (2 familia),Trichoptera (6 familia), and 5 orders of the non-EPT is the order Odonata (4 familia),Coleoptera (3 familia), Hemiptera (3 familia), Diptera (4 familia), and Neotaeniglossa(1 familia). Familia number is highest for the number familia station I found that 16familia familia and the amount was lowest for the VI station with 3 number familia.Familia number belonging to the highest station EPT group I with 8 familia EPT whilethe lowest was in the VI station with only one number familia belonging to the EPTgroup. EPT abundance ranged from 25% -100%, which is highest abundance in stationV and the lowest at the station VI. Index sensitivity level is highest at V station with thelowest index value at station 4 and the third with an index value of 3.21. Based Biotilicindex, the quality of river waters Subayang ranged from uncontaminated until beingpolluted. The results of the research can be used as enrichment Aquatic Ecologymodule.Keywords : Water Quality, Biotilic Index, Module, Aquatic Ecology